The Himalayan Conifers - IV. The Study of Soil Profiles Under Some Forest Communities in the Bashahr Himalayas - Mohan, N. P.; Puri, G. S.; Gupta, A. C. (Indian Forester, 1956)
A number of soil profiles under the main forest communities of the Bashahr Himalayas have been studied. The climax communities are : Quercus semecarpifolia Quercus incana, Quercus ilex. Besides these, mixed oak-conifer communities and pure conifer communities occurring in the areas occupied by the above climatic climaxes have also been studied. The distribution of different layers on horizons have been shown for each forest community. The amount of loss on ignition, moisture, soil relative humidity, pH and exchangeable Ca has been studied. The mean figures of the above constituents for each forest community were determined. These show very interesting differences in different forest communities. The relationship of various constituents of humus with one another was also studied. The paper marks a definite advance in our knowledge of the casual relationship of oak-conifer communities of the Himalayas with the environment.